TINJAUAN HAK KEKAYAAN INTELEKTUAL DI INDONESIA TANTANGAN DAN PROSPEK (KASUS BATIK NUSNTARA Vs JAYA FESYEN STORE) - Parningotan Malau; Agung Edy Wibowo; Rahmat A.K Purba; Andre Wijaya; Ni Putu Priscillia; Syamsul Bahari (Journal of Innovation Research and Knowledge, 2025)
Intellectual Property Rights (IPR) serve as an essential legal instrument for fostering innovation, creativity, and economic growth within a nation. In Indonesia, the IPR legal framework has evolved over time, encompassing various aspects such as copyrights, patents, trademarks, and industrial designs. Nevertheless, the implementation and enforcement of IPR in Indonesia still face several challenges, including a high rate of infringement and a lack of public awareness. This article analyzes the IPR legal framework in Indonesia, identifies the main challenges in its implementation, and discusses the prospects for future development and strengthening of the IPR system